From the Editors: Experimental designs in international business research - Zellmer-Bruhn, Mary; Caligiuri, Paula; Thomas, David C (Journal of International Business Studies, 2016)
The question that motivated this editorial was, “where are the IB experiments?” The short answer is that experiments are largely absent from the IB literature; and we argue that they shouldn’t be. Experimental methods offer the opportunity to significantly improve the evidence for the causal relationships in international business research in a variety of ways. In this article we highlight the value and limitations of experiments in IB research, and explain the basic tenets of experimental design and thinking with the goal of encouraging the submission of more papers with an experimental design to JIBS.